Predictors of care home placement in people diagnosed with dementia in a New Zealand memory service: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Cullum, Sarah; Yates, Susan; Varghese, Chris; Coomarasamy, Christin; Whittington, Rosie; Cheung, Gary
Abstract: Background: As the global population ages the burden of dementia is expected to rise across all cultures around the world. Much of the social sector costs of dementia care in high income countries is due to residential care. The aim of this study is to investigate the sociodemographic and clinical characteristics that predict care home placement in people diagnosed with dementia at a New Zealand memory service. Method: This cohort study used routinely collected clinical data gathered on referrals to the Memory Service at Middlemore Hospital in South Auckland between 2013 and 2019. Survival analysis was carried out using Cox regression models to determine significant risk factors and their associations with care home placement. Result: Comparison by ethnic group showed that NZ Europeans were on average older compared to Māori and Pacific Islanders, and were more likely to be living alone. As might be expected, age, more severe cognitive impairment and living alone were independently associated with increased risk of care home placement. After adjustment for these factors, Māori and Pacific Islanders were still less likely to be placed in a care home. People diagnosed with mixed dementia were more likely to be placed in a care home than those diagnosed with other dementia subtypes. Prescription of antipsychotics was highly associated with care home placement however we were unable to establish if antipsychotics were prescribed before or after placement. Conclusion: These data will help us to understand differences in adverse outcomes in people with dementia. The ability of Māori and Pacific Islanders to continue to care for their family member with dementia needs to be examined in more detail, as the findings might empower and enable other families to postpone care home placement.